The management and clinical outcomes of electrothermal burn injury patients over a ten-year period - Hlutkin, Aliaksandr V.; Patel, Grishma Rajendrakumar; Liyanage, L. R. Sathisha Deshan; Hnedava, Anastasiya V.; Afanasenka, Yauheni V. (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. This study investigates electrothermal burns in children, including their incidence, causes, associated systemic changes, and treatments. Electrothermal burns are unique and can be caused by factors such as moisture, leading to heat conduction from the contact site. The study aims to determine the frequency of these burns in children, identify their causes, and evaluate various treatment methods. The outcomes of interest include wound healing, scarring, and long-term complications. The results of this study will help develop better treatment strategies and reduce the incidence of such injuries. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The Grodno Regional Children’s Clinical Hospital, Belarus treated 666 children for burn injuries between 2014 and 2023, 35 of them diagnosed with electrothermal skin burns. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. According to our analysis, electrothermal burns make up approximately 5.3% of all burn injuries. Upon reviewing hos pitalization records, it was observed that the number of hospital visits related to this type of injury ranged from 3 to 5 annually, except for 2022, when there were nine recorded cases. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Our study shows that electrothermal burns are usually caused by household appliances. There is a gender imbal ance in those affected. Early detection and appropriate medical intervention are crucial in the management of these burns.